2017
DOI: 10.14260/jemds/2017/1523
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Insulin in the Diabetic Wound Ulcer of Foot and Its Comparison With Regular Normal Saline Dressing

Abstract: BACKGROUND Diabetic foot ulcers are inevitable in 15% of diabetic patients even if they follow the diet or control blood sugar level meticulously. The mainstay of treatment for diabetes related foot ulceration is a multidisciplinary team (MDT) approach that includes metabolic control, debridement, offloading/pressure redistribution, vascular control, infection control and seamless integrated wound care. And the ulcer usually is of a chronic type. With regard to topical agents, the effectiveness of topical Insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Praveen et al [22] showed the ulcer size on Day 1 was 48.33 ± 11.35 mm and 47.30 ± 11.30 mm in insulin group and saline group, respectively, and the complete healing time achieved in insulin versus saline group was 30.63 ± 6.5 days and 60.47 ± 23.31 days, respectively, with significant p value <0.0001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Praveen et al [22] showed the ulcer size on Day 1 was 48.33 ± 11.35 mm and 47.30 ± 11.30 mm in insulin group and saline group, respectively, and the complete healing time achieved in insulin versus saline group was 30.63 ± 6.5 days and 60.47 ± 23.31 days, respectively, with significant p value <0.0001.…”
Section: Discussionmentioning
confidence: 99%
“…There was a statistical difference in the initial length and breadth of the wound size among both the groups. However, final length and breadth decreased significantly in both groups, retaining the insulin group with statistically significant reduction compared to normal saline group (mean ± SD; final length: normal saline vs. insulin 47.30 ± 11.3 vs. 48.33 ± 11.35; P = 0.725, final breadth: 36.47 ± 10.94 vs. 37.4 ± 7.5; P = 0.701) [22].…”
Section: Discussionmentioning
confidence: 99%